2017
DOI: 10.1037/pas0000321
|View full text |Cite
|
Sign up to set email alerts
|

The importance and acceptability of general and maladaptive personality trait computerized assessment feedback.

Abstract: Personality traits are a useful component of clinical assessment, and have been associated with positive and negative life outcomes. Assessment of both general and maladaptive personality traits may be beneficial practice, as they may complement each other to comprehensively and accurately describe one's personality. Notably, personal preferences regarding assessment feedback have not been studied. The current study examined the acceptability of personality assessment feedback from the perspective of the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…As this represents 1 of the first efforts to do so, we were unable to find a previously validated questionnaire for assessing the relevance and acceptability of feedback and CAT administration. We developed a questionnaire that used items that had been shown to work well in the single other study we found that examined acceptability of feedback for patients completing a personality questionnaire [38]. Though we found that the questionnaire performed well during psychometric evaluation, we acknowledge that the short questionnaire may not cover all relevant aspects of questionnaire completion.…”
Section: Discussionmentioning
confidence: 99%
“…As this represents 1 of the first efforts to do so, we were unable to find a previously validated questionnaire for assessing the relevance and acceptability of feedback and CAT administration. We developed a questionnaire that used items that had been shown to work well in the single other study we found that examined acceptability of feedback for patients completing a personality questionnaire [38]. Though we found that the questionnaire performed well during psychometric evaluation, we acknowledge that the short questionnaire may not cover all relevant aspects of questionnaire completion.…”
Section: Discussionmentioning
confidence: 99%
“…A promising way to deal with such response patterns is using alternative measures that employ forced choice technique such as the Goldsmiths-60-item questionnaire [99]. [115][116][117][118][119][120][121][122][123]. In the following, we provide an updated, comprehensive summary of research on the AMPD.…”
Section: Further Issuesmentioning
confidence: 99%
“…Finally, future research may also take a patient perspective on utility and acceptability into account, which has already been carried out in research on the DSM‐5 AMPD model …”
Section: Limitations and Future Directionsmentioning
confidence: 99%